Women, unions, and social policy - Beattie, Margaret (Journal of business ethics, 1983)
We contend in this paper that the trade union role in social policy is expanding due to the debate on women's issues. The Centrale de l'enseignement du Québec is seen as a forerunner of this trend, with its policy positions on questions previously seen as ‘personal’. The method of promotion of these interests is also new, with ‘caucusing’ and ‘networking’. The significance of these changes goes beyond unionized women workers and affects all women.